PENYUSUNAN BUKU AJAR HUKUM PIDANA SEBAGAI UPAYA MENINGKATKAN KUALITAS PERKULIAHAN MAHASISWA S1 PPKN JURUSAN PMP KN FIS UNESA - Emmilia Rusdiana, ; S.h., ; Pudji Astuti, ; S.h. M.h., (Pelangi Ilmu, 2010)
Abstract : The purpose of this research is to improve the quality and quantity of the textbook. This type of research isqualitative and quantitative. Data with qualitativeresearch involving three specialists who are experts in their fieldsto provide input on the textbook in terms of improving qualityin terms of material, readability (linguistic) and pedagogical whereasin quantitative research data with the percentage of students involves the final value.